Translation and validation of the Pharmacy Services Questionnaire (PSQ) in a Chinese population - Chi Lam Cheung; Hei Hang Edmund Yiu; Frank Nim Kok Chan; Tommy Lok Hei Cho; Janet Hiu Tung Sun; Marco Tsun Lee; Tommy Ka Ho Lee; Gladys Daphne Cheung; Kitty Kit Ki Law; Janet Kit Ting Wong; Franco Wing Tak Cheng; Leo Kin Yip Lo; et al. (Journal of Pharmaceutical Policy and Practice)
Background The Pharmacy Services Questionnaire (PSQ) was developed to measure patient satisfaction with pharmaceutical care. However, it has not been translated into Cantonese-Chinese and validated in the Hong Kong population. To develop and validate a Cantonese-Chinese-translated PSQ among native Chinese patients who have used pharmacy services at community pharmacies in Hong Kong.Methods The PSQ was developed and translated into Cantonese-Chinese using iterative forward-backwards translation. Subjects were recruited by convenience sampling at three community pharmacies. Internal consistency, construct validity, discriminant validity, known-group comparison and Confirmatory Factor Analysis (CFA) were performed to confirm that the Cantonese-Chinese-translated PSQ is a valid measure of its intended constructs. Qualitative think-aloud interviews were carried out to test for comprehension and content validity. The subjects’ views and interpretation of each questionnaire item were also explored to determine the relevance, comprehensiveness, and adequacy of the response options.Results A total of 236 adult subjects were recruited to complete the Cantonese-Chinese PSQ and the Chinese 5-Level EuroQol 5-Dimension (EQ-5D-5L HK) questionnaire. Additionally, think-aloud interviews were carried out with 15 subjects. Most subjects were able to understand and interpret the Cantonese-Chinese PSQ with relative ease. The internal consistency of Cantonese-Chinese PSQ was excellent (Cronbach’s α > 0.96) for the full-scale, Friendly explanation (FE) subscale and Managing therapy (MT) subscale. CFA confirmed the hypothesised two-factor structure of the Cantonese-Chinese PSQ. Individuals with higher education levels showed statistically significantly higher satisfaction levels in the overall PSQ score and MT scale score compared to those with lower levels of education. Additionally, there was no statistically significant correlation between the Cantonese-Chinese PSQ and EQ-5D-5L HK scores, demonstrating discriminant validity.Conclusion The Cantonese-Chinese translation of the PSQ is a validated, reliable, and semantically equivalent instrument used to assess satisfaction towards services provided by community pharmacies.